The DSM-5 nonsuicidal self-injury disorder among incoming college students: Prevalence and associations with 12-month mental disorders and suicidal thoughts and behaviors - Kiekens, G.; Hasking, Penelope; Claes, L.; Mortier, P.; Auerbach, R.; Boyes, Mark; Cuijpers, P.; Demyttenaere, K.; Green, J.; Kessler, R.; Nock, M.; Bruffaerts, R. (Wiley-Liss, Inc, 2018)
Background: Approximately one in five college students report a history of nonsuicidal self-injury. However, it is unclear how many students meet criteria for the recently proposed DSM-5 nonsuicidal self-injury disorder (NSSI-D). In this study, we used full NSSI-D criteria to identify those students most in need of clinical care. Methods: Using data from the Leuven College Surveys (n = 4,565), we examined the 12-month prevalence of DSM-5 NSSI-D in a large and representative sample of incoming college students. We also explored the optimal frequency threshold as a function of interference in functioning due to NSSI, and examined comorbidity patterns with other 12-month mental disorders (i.e., major depressive disorder, broad mania, generalized anxiety disorder, panic disorder, and alcohol dependence) and suicidal thoughts and behaviors (STB). Results: Twelve-month NSSI-D prevalence was 0.8% and more common among females (1.1%) than males (0.4%). The proposed 5+ diagnostic threshold was confirmed as yielding highest discrimination between threshold and subthreshold cases in terms of distress or disability due to NSSI. A dose-response relationship was observed for NSSI recency-severity (i.e., 12-month NSSI-D, subthreshold 12-month NSSI-D, past NSSI, no history of NSSI) with number of 12-month mental disorders and STB. NSSI-D occurred without comorbid disorders for one in five individuals, and remained associated with severe role impairment when controlling for the number of comorbid disorders. Conclusions: These findings offer preliminary evidence that DSM-5 NSSI-D is uncommon among incoming college students, but may help to improve the deployment of targeted resource allocation to those most in need of services. More work examining the validity of NSSI-D is required.